Psychedelic drug abuse potential assessment for new drug applications and controlled substance scheduling: A United States perspective. (January 2023) - Henningfield, Jack E.; Ashworth, Judy; Heal, David J.; Smith, Sharon L.
Background: Psychedelics are an increasingly active area of research and pharmaceutical development. This includes abuse potential assessment to better understand their pharmacological mechanisms and effects and guide controlled substance regulation. Psychedelics pose challenges to abuse assessments to ensure valid, reliable, and generalizable outcomes and safe study conduct. Findings: Key nonclinical techniques, for example, receptor binding and functional assays in vitro, and nonclinical physical dependence determinations, are easily adaptable to psychedelics. However, the entactogens (weak reinforcers) and hallucinogens (non-reinforcers) require more flexible approaches than typically recommended by regulatory agencies. Phase 1 pharmacokinetic/pharmacodynamic safety studies and Phases 2/3 efficacy/safety trials with systematic monitoring of abuse-related adverse events are readily applicable to psychedelics. Human abuse trials require modification because supratherapeutic doses may not be safe and procedures, for example, personal monitors to manage serious adverse events, might bias outcomes. Recommendations: Abuse-related studies for psychedelics requiring approval by Food and Drug Administration and other agencies should take into consideration existing knowledge that will vary from extensive, for example, psilocybin, to zero for novel hallucinogens and entactogens. Many abuse assessments can be reasonably applied to animals and humans without compromising scientific integrity. Modification of existing techniques and incorporating a broader range of nonclinical tests should ensure generalizable outcomes. Human abuse studies merit reconsideration and possible modification to ensure safety and validity for psychedelic drug evaluation. Other nonclinical and clinical methods can provide evaluations of the pharmacological equivalence of test drugs to known drugs of abuse to provide context to the abuse assessment and guide drug scheduling.